Thermodynamic study on gas hydrates: experimental determination of equilibrium data by high-pressure microcalorimetry and modeling up to 100 MPa. - Menezes, Davi Éber Sanches de (2020)
Clathrate hydrates are crystalline structures formed by water molecules linked through hydrogen bonds. Regarding gas hydrates, the crystalline lattice hosts low molecular weight gases inside the cavities known as \"cages\". These compounds are formed at low temperature and high pressure conditions, such as those characteristic of deep water regions. Many efforts have been made in research to avoid the formation of these structures during oil and gas exploitation and transport, as these compounds may clog the flowlines. Moreover, current studies are aimed at exploiting natural reservoirs of gas hydrates as an alternative energy resource or using them for capture and sequestration of carbon dioxide, among others. However, the technology and techniques required to extract them commercially are not yet available. For that purpose, a good knowledge about their thermodynamic equilibrium is needed to predict the conditions that may favor, delay or inhibit the formation of these structures. Nevertheless, few experimental data of gas hydrate dissociation over 20 MPa are found in the literature to assess the reliability of thermodynamic models and improve their accuracy due to the instrumental limitations at extreme conditions. In this context, this work presents new data up to 100 MPa obtained by High-Pressure micro Differential Scanning Calorimetry (HP-µDSC), a relatively new technique of analysis whose application on gas hydrates studies is currently growing. Temperatures of dissociation are shown for single and double hydrates and compared to computational predictions from commercial software packages (CSMGem and Multiflash). Enthalpies of dissociation were estimated for CH4, C2H6 and CO2 single hydrates through the integration of dissociation curves from thermograms and compared to the results obtained by applying the Clapeyron equation. No data has been found so far in the literature for enthalpies of dissociation of ethane and carbon dioxide hydrates at the pressure and temperature ranges addressed in this work. Double hydrates composed of CH4-C2H6, CH4-C3H8 and CH4-CO2 were also studied, and the dissociation temperature profiles are discussed considering the occupancy degree of cages, according to the gas phase composition, and the existence of empty cavities. In systems composed of CH4-C3H8-H2O, a secondary structure, likely metastable methane hydrate, was unexpectedly formed along with the methane-propane hydrate, emphasizing the importance of the experimental study. Moreover, experiments based on the isochoric method using a PVT cell and Raman spectroscopy analyses were performed to complement the results found by microcalorimetry. Finally, methanol and imidazolium-based ionic liquids were evaluated as methane hydrate inhibitors. Although methanol has shown better efficiency in mass fraction terms, the ionic liquids usually present a dual inhibition effect when used at appropriate concentrations, with respect to the thermodynamic and kinetic behavior of gas hydrates.